ANALISIS PERMASALAHAN PELAKSANAAN PRAKTIK KERJA LAPANGAN MAHASISWA JURUSAN EKONOMI PEMBANGUNAN UNIVERSITAS NEGERI MALANG - Dika Ayu Adininggar; Achmad Ali Wafa (Jurnal Pendidikan Ekonomi, 2016)
The Internship Program is one of Social Life Subject in Department Of Economics Development which may be taken by either Study Program of Economics Education or Economic Development. Internship are a popular method of experiential learning where students practice in the real work environment which cannot be replicated in a normal classroom setting. The Internship Program is very important to increase the graduates quality, but in preparation and implementation, the problems are still faced. This research was carried out to describe some matters, included of problems happened during Internship Program, looked from the viewpoint of advising lecturer and apprentice university student. This research used descriptive qualitative research design. The data of this research was collected through interview result with informants. The data collecting was carried out by interview technique. To keep the data validity, data triangulation was carried out. Data analyzing activity was started from data organizing, data re-investigating, data processing, and data analyzing.Based on the data analyzing result, the research conclusion was gotten here. Firstly, the university students faced problem during the process in propos-ing Internship Program in administration and searching the precise instance. Sec-ondly, there was no clear work schedule during the implementation of Internship Program. Thirdly, after Internship Program, the university students felt difficult in the Final Report composing.